Indivisibility and Variety of Medical Informatics - Seelos, H.-J. (Methods of Information in Medicine, 1988)
In recent editorials it has been pointed out that medical informatics, seen as comprehensive health care informatics, should be understood as the science of information processing and engineering of automated information systems within the health care system.Since the health care system as a whole is the object system of medical informatics, its object of cognition will have to be seen in computerized medical information systems or information systems as components of socio-technical and biological object systems. Because of that and especially in view of the rapidly growing possibilities of data processing technology, the question arises how our discipline can cope with the variety in research and education. This is the subject of this opinion paper.In Leitartikeln der letzten Zeit wurde ausgeführt, daß die medizinische Informatik, aufgefaßt als “comprehensive health care informatics”, als die Wissenschaft von der Informationsverarbeitung und der Gestaltung computergestützter Informationssysteme im Gesundheitssystem verstanden werden sollte.Da das Gesundheitssystem als ganzes Objektsystem der medizinischen Informatik ist, muß der Gegenstand ihrer Erkenntnis in computergestützten medizinischen Informationssystemen bzw.. in Informationssystemen als Komponenten soziotechnischer und biologischer Objektsysteme gesehen werden. Von daher und besonders in Anbetracht der rasch zunehmenden Möglichkeiten der Datenverarbeitungstechnologie erhebt sich die Frage, wie unser Wissenszweig mit der Vielfalt in Forschung und Ausbildung fertig werden kann. Dies ist das Thema dieses Beitrags.
Keywords: Medical Informatics; Systems